EVALUATION OF SUSTAINABILITY ASSESSMENT POST CHANGES IN THE MANAGEMENT OF THE NATURAL RESERVE TO THE NATURAL TOURISM PARK IN KAMOJANG AREA, WEST JAVA, INDONESIA - Hindayani, Purna; Bratanegara, Alnidi Safarach; Putri, Intan Adhi Perdana; Anna, Zuzy; Pratama, Armandha Redo (Journal of Environmental Science and Sustainable Development, 2025)
The area of Kamojang Nature Tourism Park, which was originally only 255 hectares, has expanded to 2,391 hectares following a changes in the Nature Reserve area. This change has raised concerns and objections from various parties, as it is considered to open opportunities for exploitation, threaten biodiversity, and potentially trigger tourism activities that may degrade the environmental quality of the areaThis study aims to analyze the sustainability status index of the Kamojang Natural Tourism Park following the status downgrade from a Nature Reserve to a Natural Tourism Park. A descriptive qualitative approach used, utilizing the Multi-dimensional Scaling model to determine sustainability status. The sustainability index status of the Natural Tourism Park of Kamojang is subdivided from each of dimensions: natural tourism management, ecological or environmental, economic, disaster, socio-culture aspects. In addition, this study identifies sensitive attributes that influence the sustainability status of the Natural Tourism Park of Kamojang, which serve as a basis for developing appropriate policies to ensure the sustainable and conserved Natural Tourism Park (NTP). The results show that the sustainability index status across all five dimensions are below 50 which derived from five dimensions (tourism management, disaster, ecology/environment, economy, socio-culture) that the status is regarded as bad and less sustainable specifically of the NTP situated in of Pasirwangi, Paseh, Pacet and Kertasari sub-districts. These finding highlights the critical need for integrated, and multidimensional interventions to address systemic vulnerabilities and promote sustainable development within rural tourism ecosystems. Therefore, a comprehensive strategy for sustainable tourism development is essential in various aspects ranging from planning, capability and land feasibility to determining the carrying capacity and mitigation as well as developing activities and tourist attractions.